The impact of anaphylaxis on the absorption of intranasal epinephrine in anaesthetized non-naive beagle dogs - Samantha Sparapani, MSc, PhD; Simon Authier, DMV, MBA, PhD; Richard Lowenthal, MS, MBA; Sarina Tanimoto, MD, PhD (Journal of Allergy and Clinical Immunology: Global, 2023)
Background: Epinephrine delivery via an intranasal spray (neffy) is being evaluated as an additional option to treat severe allergic reaction and may provide clinical benefit by reducing the time to dosing in community settings by avoiding needles. Given that hypotension is a hallmark symptom of severe allergic reactions, a preclinical study was conducted to evaluate the impact of this factor on epinephrine absorption via neffy. Objective: The objective of this study was to evaluate the absorption of epinephrine via neffy in a dog model of anaphylaxis with severe hypotension. Methods: Epinephrine absorption via neffy was evaluated in anesthetized beagle dogs under both normal conditions and hypotension associated with anaphylaxis. A total of 14 dogs (10 males and 4 females) were dosed with neffy, 1.0 mg, under normal conditions, followed by neffy, 1.0 mg, under conditions of anaphylaxis. Results: The mean maximum concentration of epinephrine was higher during anaphylaxis than under normal conditions (2,670 ± 2,150 pg/mL and 1,330 ± 739 pg/mL [P < .05]). Relative to normal conditions, anaphylaxis resulted in higher overall epinephrine exposure (area under the curve from 0 to 45 minutes = 54,400 ± 18,100 min × pg/mL and 34,300 ± 21,500 minutes × pg/mL [P < .05]), which is likely due to the increase in vascular permeability commonly observed during severe allergic reactions. Conclusion: Taken together with real-world evidence from nasal naloxone treatment for opioid overdose demonstrating that the reduced blood flow or hypotension associated with overdose does not appear to suppress naloxone’s efficacy, the current findings demonstrate that epinephrine is well absorbed following neffy delivery during the hypotension associated with severe anaphylaxis reactions.